Prevalence of Diabetes Mellitus, Hypertension, and Dyslipidemia in Student-Run Screening Clinics for Rural Communities in the Sierra Norte of Puebla, Mexico - Sean Navin; Daniel Tomaszewski (Journal of Student-Run Clinics, 2018)
Background: The growing prevalence of hypertension (HTN), diabetes mellitus (DM), and dyslipidemia in Mexico highlights the need for preventative health care services. Rural communities worldwide lack access to such services. The purpose of this study was to describe the prevalence of HTN, DM, and dyslipidemia in student-run screening clinics in rural communities of the Sierra Norte of Puebla, Mexico to better understand the role the clinics play for the patients served.Methods: Data were collected from patients from rural, Mexican towns participating in free pharmacy student-run screening clinics. Patients consented to have their de-identified information pooled for research. Screenings included blood pressure readings, blood glucose levels, hemoglobin A1C values, and cholesterol levels.Results: Records from 483 patients were used from a total of 12 clinics. The prevalence of HTN was 38.3%, DM was 20.3%, and dyslipidemia was 45%. The median total cholesterol was 169 mg/dL, triglycerides were 180.5 mg/dL, HDL was 38 mg/dL, and LDL was 88 mg/dL. The most frequent lipid panel abnormality was hypertriglyceridemia with a prevalence of 66.3% followed by low HDL with a prevalence of 55.8%, and hypercholesterolemia was 24.4%.Conclusions: There was a high prevalence of DM, HTN, and dyslipidemia in pharmacy student-run screening clinics in rural communities of the Sierra Norte of Puebla, Mexico. Future studies should evaluate patient access to primary care and health insurance coverage in order to better understand the value of these student-run clinics in the context of local resources.